2001
DOI: 10.2337/diacare.24.4.678
|View full text |Cite
|
Sign up to set email alerts
|

Disordered Eating, Body Mass, and Glycemic Control in Adolescents With Type 1 Diabetes

Abstract: OBJECTIVE -To examine the relationship between disordered eating attitudes and behaviors, BMI, and glycemic control in adolescents with type 1 diabetes.RESEARCH DESIGN AND METHODS -In a cross-sectional design, 152 adolescents (ages 11-19 years) completed three scales from the Eating Disorders Inventory (EDI): Body Dissatisfaction, Drive for Thinness, and Bulimia. All subjects had diabetes for Ͼ1 year. Glycemic control was assessed by glycosylated hemoglobin (HbA 1c ). Height and weight were measured to assess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
104
3
13

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(136 citation statements)
references
References 30 publications
(47 reference statements)
16
104
3
13
Order By: Relevance
“…Substantial fluctuations in blood glucose and insulin levels may cause changes in eating behavior, which has also been shown in several studies. [10][11][12][13][14] Without sufficient insulin, glucose has no ability to get into the cells to be used or to be stored in the cell, resulting in hyperglycemia and an increase in hunger. Likewise, exogenous insulin administration results in hunger along with an increased appetite, which is reflected in eating behavior changes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Substantial fluctuations in blood glucose and insulin levels may cause changes in eating behavior, which has also been shown in several studies. [10][11][12][13][14] Without sufficient insulin, glucose has no ability to get into the cells to be used or to be stored in the cell, resulting in hyperglycemia and an increase in hunger. Likewise, exogenous insulin administration results in hunger along with an increased appetite, which is reflected in eating behavior changes.…”
Section: Discussionmentioning
confidence: 99%
“…The maximum possible score is 30 for Symptom Scale. A symptom score of 20 or more indicates the presence of binge eating; the medium range (10)(11)(12)(13)(14)(15)(16)(17)(18)(19) suggests an unusual eating pattern; the low range (0-10) falls within normal limits. The BITE is a well-validated and reliable instrument: the inter-item reliability coefficient was 0.96 for the symptom subscale and the test-retest reliability was 0.86 and 0.68 for non-clinical and clinical groups, respectively.…”
Section: Eating Attitudes Test (Eat): Developed Bymentioning
confidence: 99%
See 1 more Smart Citation
“…A study of healthy children (Bernier et al 2010) also demonstrated similar correlations between BMI percentile and overall body esteem (r ¼ À0.36 to À0.45, p < 0.01); however, those children demonstrated a negative correlation between BMI percentile and scores on the ChEAT (r ¼ À0.22 to À28, p < 0.01). When comparing to patients with chronic metabolic disease, previous research involving patients with Type I diabetes has noted that body dissatisfaction is associated with poor glycemic control, whereas good metabolic control is linked to better quality of life (Meltzer et al 2001;Hoey et al 2001). Poor metabolic control in GSD leads to greater complications and comorbid factors including hypoglycemic episodes, hepatomegaly, hyperlipidemia, hyperlactatemia, nephropathy, and hepatic adeno-mas, which may negatively impact quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Ensaios clínicos com adultos mostraram que insulinas de ação basal como a Detemir parecem causar menos ganho de peso do que a insulina NPH, em esquema com insulina de ação basal e insulina de ação ultra-rápida (HERMANSEN et al, 2004). E já se sabe que maior peso ou IMC podem ser preditores para risco de TA (Meltzer et al, 2001).…”
Section: Discussionunclassified